=8p-2(7q-3p)

Simple and best practice solution for =8p-2(7q-3p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =8p-2(7q-3p) equation:


Simplifying
0 = 8p + -2(7q + -3p)

Reorder the terms:
0 = 8p + -2(-3p + 7q)
0 = 8p + (-3p * -2 + 7q * -2)
0 = 8p + (6p + -14q)

Combine like terms: 8p + 6p = 14p
0 = 14p + -14q

Solving
0 = 14p + -14q

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-14p' to each side of the equation.
0 + -14p = 14p + -14p + -14q
Remove the zero:
-14p = 14p + -14p + -14q

Combine like terms: 14p + -14p = 0
-14p = 0 + -14q
-14p = -14q

Divide each side by '-14'.
p = q

Simplifying
p = q

See similar equations:

| X^4-3x^3-6x^2+3x+1=0 | | Iy=28 | | 3x^2-x-5x=0 | | x^2+24x+39=0 | | 3(x)-y=9 | | 5x+75-2x= | | (Sin(6x))+(sin(2x))=0 | | 456-p=321 | | 3.61x=6+2.247x | | -8x-3=3+8x | | 5x^5-5x^3-30x=0 | | 12x^2+8x+4=0 | | 12x^2+4x=y | | 12x^2+8x+4=y | | 10pq-20pq= | | f(x)f(y)=f(x+y)+f(x-y) | | 35+3x=6(9x+8) | | -5(6d+9)=-19 | | 9-8(1+3c)=24 | | -9(1+2f)=34 | | 29=8z-6z | | 2x^4+11x^2y^2-6y^4=0 | | 35=6+2(b-7) | | -4s+7-8=34 | | 4k-8k=-34 | | -5a+7+8a=-16 | | 5(4n-9)=32-7n | | 7(2c-8)=-18 | | -32=3+6(n+8) | | 2+6(1-7k)=27 | | 8(6s+9)=28+4s | | -5h+3-6h=-34 |

Equations solver categories